Wire fin heat exchanger using aluminium fumarate for adsorption heat pumps. (5th January 2020) - Saleh, Majdi M.; Al-Dadah, Raya; Mahmoud, Saad; Elsayed, Eman; El-Samni, Osama
Highlights: Results showed that wire fin heat exchanger had a better performance than others. Aluminium fumarate packed fin wire heat exchanger optimum design was proposed. Increasing fin height, spacing and tube diam. adversely affected the performance. Abstract: Adsorption heat pumps have faced major challenges in terms of their large size and capital cost caused by using conventional heat exchangers for adsorption beds and the poor performance of the currently used adsorbent materials such as silica gel and zeolite. This work experimentally and numerically investigates the performance of a wire finned heat exchanger compared to rectangular finned and microchannel heat exchangers. The microchannel heat exchanger experienced significantly high pressure drop almost 5 times that of the wire and rectangular finned heat exchangers. The two heat exchangers were packed with aluminium fumarate metal-organic framework (MOF) material where the finned wire heat exchanger had a superior performance. Then the performance of the wire finned heat exchanger packed with aluminium fumarate was investigated in terms of water uptake and surface temperature at various fin height (3.5, 7 and 14 mm), spacing (1, 2 and 3.5 mm) and tube diameter (6, 9 and 12 mm). The numerical model was validated using experimental work showing good agreement with deviation ranging from ±10.